The Challenges of Caring for an Adult Child with Schizophrenia in the Family: An Analysis of the Lived Experiences of Older Parents - Mehdi Sharifi PhD Student; Seyyed Jalal Younesi PhD, Associate Professor; Mahshid Foroughan MD, Professor; Mohammad Hadi Safi PhD, Assistant Professor; Mohammad Saeed Khanjani PhD, Associate Professor (SAGE Publishing, 2023)
The present study aimed to investigate the lived experiences of older parents regarding the challenges in caring for adult children with schizophrenia. The current study was conducted on 16 parental (mother or father) caregivers of adult children with schizophrenia using a descriptive phenomenological qualitative approach and Colaizzi's seven-step method. This study follows the Qualitative Research Checklist (COREQ). The findings showed that the parent caregivers' experiences could be classified into two main themes: "burden of care" and "Negative attitude and inefficient performance." The former consisted of three sub-themes including "disrupted social and family interactions," "helplessness and inefficient support," and "challenges of the healthcare system," while the latter had two sub-themes including "Negative attitude and inefficient performance of the caregivers" and "Negative attitude and inefficient performance of families and society." Older parents have to tolerate a significant burden of care due to their age and physical conditions. Improving the knowledge of specialists, the government's redoubled efforts in multifaceted support for patients and caregivers, creating an integrated team of specialists, and accepting and improving public attitudes against stigma and obvious discrimination in society as important priorities in improving the condition of caregivers and patients with schizophrenia were considered.